2004
DOI: 10.1002/jat.981
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation of a new allergy vaccine containing the adjuvant monophosphoryl lipid A (MPL®) for the treatment of grass pollen allergy

Abstract: A novel allergy vaccine (Pollinex Quattro) has been developed for the prevention or relief of allergic symptoms caused by a variety of pollens. Within this range, the grass pollen allergy vaccine contains extracts of 12 grass pollens and rye cereal (all chemically modified by glutaraldehyde) that are adsorbed onto L-tyrosine with addition of the immunostimulatory adjuvant monophosphoryl lipid A (MPL). A specific preclinical safety testing strategy was developed to support clinical use, comprising single-dose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…This finding, together with raised white blood cell count and associated increased neutrophil count, increased globulin level, and reduced albumin/globulin ratio, also observed in our study, has been considered associated to stimulation of the immune system, and could be considered as indicators of the immunological action of the adjuvants (Baldrick et al, 2004). Recently, it was found that VSSP adjuvant induced a significant splenomegaly in mice due to accumulation of CD11b + Gr-1 + cells (Fernández et al, 2011).…”
Section: Daysupporting
confidence: 65%
“…This finding, together with raised white blood cell count and associated increased neutrophil count, increased globulin level, and reduced albumin/globulin ratio, also observed in our study, has been considered associated to stimulation of the immune system, and could be considered as indicators of the immunological action of the adjuvants (Baldrick et al, 2004). Recently, it was found that VSSP adjuvant induced a significant splenomegaly in mice due to accumulation of CD11b + Gr-1 + cells (Fernández et al, 2011).…”
Section: Daysupporting
confidence: 65%
“…To 1 HD DTaP vaccine, 2 ml of 100 g/ml MPL-PBS was added. The amount of MPL administered is less than the amount that showed no toxicological effects in a single-dose toxicity study (2).…”
Section: Vaccines and Adjuvants (I) Seriesmentioning
confidence: 90%
“…The nontoxic LPS derivative monophosphoryl lipid A (MPL) engages TLR4 (17,33), inducing Th1 adaptive immunity and changing Th2-directed responses to Th1-directed responses (3,34,38,48). MPL combined with aluminum (denoted AS04) is registered for clinical use as an adjuvant in viral vaccines, such as the hepatitis B virus vaccine (6) and the human papillomavirus vaccine (18), while MPL combined with L-tyrosine is registered for clinical use as an adjuvant in allergy therapy (2,27). Furthermore, a Neisseria meningitidis strain deficient for the late acyltransferase LpxL2 displayed a strongly decreased endotoxic activity when it was tested for its ability to stimulate human macrophages (46).…”
mentioning
confidence: 99%
“…These components are well-characterized agonists of innate immunity receptors and are most likely responsible for the ability of PL to induce DC maturation (Rodrıguez et al 2005). Therefore, increased leukocyte stimulation and increase in spleen weight following three doses of the vaccine were not unexpected, considering that PL has potent immunostimulatory effects (Rodrıguez et al 2005; Bracho Animal studies evaluating potential toxicity of an allergen vaccine containing a LPS-derived monophosphoryl Lipid A (MPL) have described also remarked increases in host white blood cell levels and spleen weight (Baldrick et al 2002(Baldrick et al , 2004(Baldrick et al , 2007. Nevertheless, clinical trials of this MPL-containing allergen vaccine revealed a satisfactory safety profile for use in subcutaneous injection immunotherapy in patients suffering from grass pollen allergy (Rosewich et al 2010(Rosewich et al , 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Aluminum salts, used for many years in human vaccines, are known to produce local reactions in animals and humans and this is known to be associated with their mechanism of adjuvanticity (HogenEsch 2013;JensenJarolim 2015). Novel adjuvants, such as MPL, also induce a local inflammatory response with foreign body granulomas characterized by aggregated macrophages, polymorphonuclear cells, necrotic debris, and cellulites/fibrosis (Baldrick et al 2002(Baldrick et al , 2004). Allergen-specific IgE levels in serum.…”
Section: Discussionmentioning
confidence: 99%